2010
DOI: 10.1517/17530051003725113
|View full text |Cite
|
Sign up to set email alerts
|

New biomarkers for lung cancer

Abstract: Although some markers seem to be promising, at present there is no consensus on the proven value of their clinical use in lung cancer. The future lies probably in a panel of biomarkers instead of individual assays, or in predictive models derived from the integration of clinical variables and gene expression profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 222 publications
1
5
0
Order By: Relevance
“…Carcinoma embryonic antigen (CEA) is one of the currently available biomarkers for lung adenocarcinoma. It has been reported that the sensitivity and specificity of CEA are 69% and 68%, respectively [26]. Similar levels of specificity and sensitivity were achieved for PGE-MUM.…”
Section: Discussionsupporting
confidence: 67%
“…Carcinoma embryonic antigen (CEA) is one of the currently available biomarkers for lung adenocarcinoma. It has been reported that the sensitivity and specificity of CEA are 69% and 68%, respectively [26]. Similar levels of specificity and sensitivity were achieved for PGE-MUM.…”
Section: Discussionsupporting
confidence: 67%
“…The online literature database PubMed was used to identify lung cancer miRNA expression profiling studies published from January 2003 until May 2014 (last accessed on 15 May 2014), by means of the 'Medical Subject Heading' terms: 'NSCLC' and 'microRNAs' in combination with the keywords 'profiling' and 'humans'. The results of previous studies to identify circulating miRNAs specific to lung cancer were inconsistent (24)(25)(26)(27), and potential biomarkers remain to be elucidated and exploited. Based on these previous findings, a list of 15 miRNAs was compiled, whose expression has already been reported as deregulated in cancer, or has not been investigated (Table III).…”
Section: Methodsmentioning
confidence: 99%
“…However, in practice, this system often fails in providing sufficient sensitivity and information of value for optimal screening. For example, for the diagnosis of lung cancer, CEACAM sensitivity and specificity is 69% and 68% respectively, while that for CYFRA 21-1 was 43% and 89%, respectively [ 27 ]. Diagnostic sensitivity of plasma ProGRP in distinguishing SCLC was estimated to be approximately 84%, and specificity 95% [ 28 ].…”
Section: Circulating Biomarkers Of Carcinogenesismentioning
confidence: 99%